Double 85-resistant long carbon chain nylon material as well as preparation method and application thereof

The two-layer co-extrusion process with a long carbon chain nylon material and TPE, enhanced by compatibilizers and epoxy resin, addresses bonding issues in cooling pipes, achieving robust durability under extreme conditions.

CN119242036AActive Publication Date: 2025-01-03ORINKO HIGH PERFORMANCE MATERIALS TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411511641.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-03
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

Existing cooling pipes in new energy batteries face challenges in maintaining strong bonding between the inner layer of long carbon chain nylon and the outer layer of TPE due to issues with adhesion and environmental durability, particularly under high temperature and high humidity conditions.

Method used

A two-layer co-extrusion process is employed using a long carbon chain nylon material composed of specific components, including PA1012, epoxy resin, and TPE, with the addition of compatibilizers and nylon hot melt adhesive to enhance molecular interaction and bonding strength.

Benefits of technology

The solution significantly improves the bonding strength and durability of the composite material, ensuring excellent stability and durability under harsh environmental conditions, such as high temperature and high humidity, by utilizing specific compatibilizers and epoxy resins to enhance molecular interaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005105629480000011
    Figure BDA0005105629480000011
  • Figure BDA0005105629480000021
    Figure BDA0005105629480000021
  • Figure BDA0005105629480000091
    Figure BDA0005105629480000091
Patent Text Reader

Abstract

The invention discloses a double-85-resistant long carbon chain nylon material as well as a preparation method and application thereof. The double-85-resistant long carbon chain nylon material is prepared from the following components in percentage by mass: 5-12% of a compatilizer, 3-10% of epoxy resin, 3-10% of a nylon hot melt adhesive, 1-3% of a coloring agent, 0.2-1% of an antioxidant, 0.2-0.7% of a lubricant, 0.2-0.5% of a heat stabilizer and the balance of polyamide resin. Through the innovative material and process design, the bonding strength of the bonding layer between the long-chain nylon and the thermoplastic elastomer (TPE) can be remarkably improved, and it is ensured that the key connecting part can still maintain the excellent bonding performance without failure even though the key connecting part is subjected to long-term high-temperature, high-humidity and other extreme environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, in particular to a long carbon chain nylon material resistant to double 85 and a preparation method and application thereof. Background Art

[0002] In new energy batteries, many cooling pipes belong to suspension structures. In order to meet the shock absorption requirements, a layer of TPE material is injected on the outside as a shock absorption layer. The present invention adopts a co-extrusion scheme, abandons the traditional three-layer co-extrusion, and realizes two-layer co-extrusion. Through modification, the surface of PA1012 is active during extrusion, and it is tightly bonded with TPE through active functional groups, and then assisted by the water resistance of hot melt adhesive to achieve double "85" 1000H without separation. The present invention uses the excellent flexibility, excellent low temperature resistance, low water absorption and excellent chemical resistance of long carbon chain nylon to make the inner layer material of the pipe. TPE uses its sealing properties to play a sealing, fixing and shock absorption role in the card slot. The long carbon chain nylon and TPE are made into inner and outer layer pipelines that are tightly connected. In view of the low degree of localization of PA12 and PA11, we chose PA1012, which is relatively cheap and has been maturely mass-produced in China, to achieve complete localization. Summary of the invention

[0003] Based on this, the purpose of the present invention is to provide an extrusion-grade long carbon chain nylon material resistant to double 85 and TPE-adhesive and a preparation method thereof to solve the problems raised in the above background technology.

[0004] To achieve the above object, the present invention provides the following technical solutions:

[0005] In the first aspect, the present invention discloses a long carbon chain nylon material resistant to double 85, which is prepared from the following components according to mass percentage:

[0006]

[0007]

[0008] The epoxy resin is preferably at least one of 6101 (Baling Petrochemical), SM601 (Jiangsu Runfeng), SM609 (Jiangsu Sanmu) and NPCN-704 (Taiwan Nanya), and the nylon hot melt adhesive is preferably at least one of 2A (EMS), 2513 (Arkema), PA812 and PA801 (Nantong Xinxing). As a further embodiment of the present invention: the compatibilizer is one or more of grafted POE, grafted EPDM, grafted PP and grafted SEBS.

[0009] As a further solution of the present invention: the lubricant is at least one or more of PETS, OP wax, silicone, silicone oil and silicone amide.

[0010] As a further embodiment of the present invention: the antioxidant includes a main antioxidant and an auxiliary antioxidant, the main antioxidant is at least one or more of antioxidant 245, antioxidant 1010, antioxidant 1098, and antioxidant 9228, and the auxiliary antioxidant is at least one of antioxidant 168 and antioxidant 626.

[0011] As a further embodiment of the present invention: the heat stabilizer is at least one or more of an inorganic copper salt nylon heat stabilizer, an organic copper salt nylon heat stabilizer, an inorganic phosphate nylon heat stabilizer, a titanate-treated aluminum silicate and a dipentaerythritol [3-(3.5-tert-butyl-4-hydroxyphenyl) propionate] composite heat stabilizer.

[0012] As a further solution of the present invention: the polyamide resin is PA1012 high-viscosity resin, and its relative viscosity is 4-8.

[0013] As a further solution of the present invention: the colorant is at least one or more of nylon carrier aniline black masterbatch and PE carrier black masterbatch.

[0014] In a second aspect, the present invention discloses a method for preparing the above-mentioned long carbon chain nylon material resistant to double 85, comprising the following steps:

[0015] Weigh each component according to mass percentage, mix the polyamide resin, compatibilizer, epoxy resin and colorant evenly, then add lubricant, primary antioxidant, secondary antioxidant, heat stabilizer and nylon hot melt adhesive powder and mix evenly to obtain a mixture;

[0016] The mixed material is added into the main feeding port of a twin-screw extruder, and after melting, extrusion, cooling, air drying, and pelletizing, an extrusion-grade long carbon chain nylon material resistant to double 85 and capable of adhering to TPE is obtained;

[0017] Among them, the temperature of the twin-screw extruder from the first zone to the head is 210℃, 225℃, 230℃, 235℃, 240℃, 245℃, 245℃, 245℃, 245℃, 245℃, 245℃, 245℃; the screw speed is 400 rpm and the feeding is 35-45 rpm.

[0018] In a third aspect, the present invention discloses an application of the above-mentioned long-carbon-chain nylon material resistant to double 85 in a double-layer co-extruded material, wherein the double-layer co-extruded material comprises an inner tube and an outer tube, wherein the inner tube is made of the long-carbon-chain nylon material as described in any one of claims 1 to 7, and the outer tube is made of TPE resin.

[0019] As a further solution of the present invention: the hardness of the TPE resin is 65-70, and its 200H compression rate is less than 2% under the conditions of 110°C and 1.8kN.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The present invention can significantly improve the bonding strength of the bonding layer between long-chain nylon and thermoplastic elastomer (TPE) through innovative material and process design, ensuring that this key connection can maintain its excellent bonding performance without failure even under long-term extreme environmental tests such as high temperature and high humidity. Specifically, the present invention introduces specific compatibilizers and epoxy resins to improve the molecular interaction between the two materials, thereby greatly improving the bonding strength between them, so that the composite material products composed of long-chain nylon and TPE can show excellent stability and durability in a variety of harsh application environments. DETAILED DESCRIPTION

[0022] For ease of understanding of the present invention, the present invention will be described more fully below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.

[0023] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0024] The specific information of the raw materials used in the following examples and comparative examples is as follows:

[0025] The lubricant is silicone masterbatch, produced by Chengdu Silike Technology Co., Ltd., with the brand name LYSI-306;

[0026] The main antioxidant is antioxidant 1098, produced by Tianjin Lianlong;

[0027] The auxiliary antioxidant is antioxidant 168, produced by Tianjin Lianlong;

[0028] Heat stabilizer, manufactured by Brüggemann, brand name H318;

[0029] Colorant, manufactured by Colloids, brand number N1033;

[0030] PA1012 high viscosity resin, produced by Shandong Dongchen, brand PA1012 high viscosity, relative viscosity 6;

[0031] Compatibilizer, manufactured by Nengzhiguang, brand name X-042;

[0032] Epoxy resin, manufactured by Baling Petrochemical, brand 6101;

[0033] Nylon hot melt adhesive, manufactured by Nantong Xinxing, brand PA801;

[0034] The TPE resin has a hardness of 68A. Preferably, its 200H compression rate at 110°C and 1.8kN is less than 2%.

[0035] All materials are commercially available common products.

[0036] It is to be understood that the above raw materials and reagents are only examples of some specific embodiments of the present invention, so that the technical solution of the present invention is clearer, and it does not mean that the present invention can only use the above reagents, and the specific scope in the claims shall prevail. In addition, the "parts" described in the examples and comparative examples, unless otherwise specified, refer to parts by weight.

[0037] Any range described in the present invention includes the end value and any numerical value between the end values ​​and any sub-range formed by the end value or any numerical value between the end values.

[0038] Example 1

[0039] (1) Weighing materials: First, dry PA1012 high-viscosity resin at 80°C for 4 hours for later use; then weigh the following raw materials: 5 parts of compatibilizer, 0.5 parts of lubricant, 0.3 parts of primary antioxidant, 0.2 parts of secondary antioxidant, 0.3 parts of thermal stabilizer, 10 parts of epoxy resin, 5 parts of nylon hot melt adhesive, 1.5 parts of colorant, and 77.2 parts of PA1012 high-viscosity resin;

[0040] (2) Mixing: Add weighed PA1012 high-viscosity resin, compatibilizer, epoxy resin, and colorant into a high-speed mixer and mix at high speed for 5 minutes, then add weighed nylon hot melt adhesive, lubricant, primary antioxidant, auxiliary antioxidant, and thermal stabilizer and continue to mix at high speed for 5 minutes to obtain a mixture;

[0041] (3) Melt extrusion: the mixed material is added into a twin-screw extruder, and the temperature of the twin-screw extruder is 210° C., 225° C., 230° C., 235° C., 240° C., 245° C., 245° C., 245° C., 245° C., 245° C., 245° C., 245° C. from the first zone to the die head; the screw speed is 400 rpm and the feed rate is 35-45 rpm.

[0042] (4) Extrusion pelletizing: The extruded material is cooled, air-dried, pelletized, passed through a vibrating screen, homogenized and packaged in a homogenizing tank to obtain the finished product, i.e., the long carbon chain nylon material.

[0043] Example 2

[0044] Weighing materials: first dry the PA1012 high viscosity resin at 80℃ for 4 hours for use, then weigh the raw materials: 9 parts of compatibilizer, 0.5 parts of lubricant, 0.3 parts of primary antioxidant, 0.2 parts of auxiliary antioxidant, 0.3 parts of thermal stabilizer, 6 parts of epoxy resin, 5 parts of nylon hot melt adhesive, 1.5 parts of colorant, and 77.2 parts of PA1012 high viscosity resin.

[0045] Mixing: Add weighed PA1012 high-viscosity resin, compatibilizer, epoxy resin, and colorant into a high-speed mixer and mix at high speed for 5 minutes. Then add weighed nylon hot melt adhesive, lubricant, primary antioxidant, auxiliary antioxidant, and thermal stabilizer and continue mixing at high speed for 5 minutes to obtain a mixture.

[0046] Melt extrusion: the mixture is added into a twin-screw extruder, and the temperature of the twin-screw extruder is 210°C, 225°C, 230°C, 235°C, 240°C, 245°C, 245°C, 245°C, 245°C, 245°C, 245°C, 245°C from the first zone to the die head; the screw speed is 400 rpm and the feeding is 35-45 rpm.

[0047] Extrusion pelletizing: The extruded material is cooled, air-dried, pelletized, passed through a vibrating screen, homogenized and packaged in a homogenizing tank to obtain the finished product, that is, the long carbon chain nylon material.

[0048] Example 3

[0049] Weighing materials: first dry the PA1012 high viscosity resin at 80°C for 4 hours for use; then weigh the raw materials: 12 parts of compatibilizer, 0.5 parts of lubricant, 0.3 parts of primary antioxidant, 0.2 parts of auxiliary antioxidant, 0.3 parts of thermal stabilizer, 3 parts of epoxy resin, 5 parts of nylon hot melt adhesive, 1.5 parts of colorant, and 77.2 parts of PA1012 high viscosity resin.

[0050] Mixing: Add weighed PA1012 high-viscosity resin, compatibilizer, epoxy resin, and colorant into a high-speed mixer and mix at high speed for 5 minutes. Then add weighed nylon hot melt adhesive, lubricant, primary antioxidant, auxiliary antioxidant, and thermal stabilizer and continue mixing at high speed for 5 minutes to obtain a mixture.

[0051] Melt extrusion: the mixture is added into a twin-screw extruder, and the temperature of the twin-screw extruder is 210°C, 225°C, 230°C, 235°C, 240°C, 245°C, 245°C, 245°C, 245°C, 245°C, 245°C, 245°C from the first zone to the die head; the screw speed is 400 rpm and the feeding is 35-45 rpm.

[0052] Extrusion pelletizing: The extruded material is cooled, air-dried, pelletized, passed through a vibrating screen, homogenized and packaged in a homogenizing tank to obtain the finished product, that is, the long carbon chain nylon material.

[0053] Example 4

[0054] First, dry the PA1012 high-viscosity resin at 80°C for 4 hours for use, and then weigh the following raw materials: 7 parts of compatibilizer, 0.5 parts of lubricant, 0.3 parts of primary antioxidant, 0.2 parts of secondary antioxidant, 0.3 parts of thermal stabilizer, 5 parts of epoxy resin, 5 parts of nylon hot melt adhesive, 1.5 parts of colorant, and 80.2 parts of PA1012 high-viscosity resin.

[0055] Mixing: Add weighed PA1012 high-viscosity resin, compatibilizer, epoxy resin, and colorant into a high-speed mixer and mix at high speed for 5 minutes. Then add weighed nylon hot melt adhesive, lubricant, primary antioxidant, auxiliary antioxidant, and thermal stabilizer and continue mixing at high speed for 5 minutes to obtain a mixture.

[0056] Melt extrusion: the mixture is added into a twin-screw extruder, and the temperature of the twin-screw extruder is 210°C, 225°C, 230°C, 235°C, 240°C, 245°C, 245°C, 245°C, 245°C, 245°C, 245°C, 245°C from the first zone to the die head; the screw speed is 400 rpm and the feeding is 35-45 rpm.

[0057] Extrusion pelletizing: The extruded material is cooled, air-dried, pelletized, passed through a vibrating screen, homogenized and packaged in a homogenizing tank to obtain the finished product, that is, the long carbon chain nylon material.

[0058] Comparative Example 1

[0059] Weighing materials: first dry the PA1012 high viscosity resin at 80°C for 4 hours for use; then weigh the raw materials: 5 parts of compatibilizer, 0.5 parts of lubricant, 0.3 parts of primary antioxidant, 0.2 parts of auxiliary antioxidant, 0.3 parts of thermal stabilizer, 10 parts of epoxy resin, 1.5 parts of colorant, and 82.2 parts of PA1012 high viscosity resin.

[0060] Mixing: Add weighed PA1012 high-viscosity resin, compatibilizer, epoxy resin, and colorant into a high-speed mixer and mix at high speed for 5 minutes. Then add weighed lubricant, primary antioxidant, auxiliary antioxidant, and thermal stabilizer and continue mixing at high speed for 5 minutes to obtain a mixture.

[0061] Melt extrusion: the mixture is added into a twin-screw extruder, and the temperature of the twin-screw extruder is 210°C, 225°C, 230°C, 235°C, 240°C, 245°C, 245°C, 245°C, 245°C, 245°C, 245°C, 245°C from the first zone to the die head; the screw speed is 400 rpm and the feeding is 35-45 rpm.

[0062] Extrusion pelletizing: The extruded material is cooled, air-dried, pelletized, passed through a vibrating screen, homogenized and packaged in a homogenizing tank to obtain the finished product, that is, the long carbon chain nylon material.

[0063] Comparative Example 2

[0064] Weighing materials: first dry the PA1012 high viscosity resin at 80°C for 4 hours for use; then weigh the raw materials: 3 parts of compatibilizer, 0.5 parts of lubricant, 0.3 parts of primary antioxidant, 0.2 parts of auxiliary antioxidant, 0.3 parts of thermal stabilizer, 13 parts of epoxy resin, 5 parts of nylon hot melt adhesive, 1.5 parts of colorant, and 76.2 parts of PA1012 high viscosity resin.

[0065] Mixing: Add weighed PA1012 high-viscosity resin, compatibilizer, epoxy resin, and colorant into a high-speed mixer and mix at high speed for 5 minutes. Then add weighed nylon hot melt adhesive, lubricant, primary antioxidant, auxiliary antioxidant, and thermal stabilizer and continue mixing at high speed for 5 minutes to obtain a mixture.

[0066] Melt extrusion: the mixture is added into a twin-screw extruder, and the temperature of the twin-screw extruder is 210°C, 225°C, 230°C, 235°C, 240°C, 245°C, 245°C, 245°C, 245°C, 245°C, 245°C, 245°C from the first zone to the die head; the screw speed is 400 rpm and the feeding is 35-45 rpm.

[0067] Extrusion pelletizing: The extruded material is cooled, air-dried, pelletized, passed through a vibrating screen, homogenized and packaged in a homogenizing tank to obtain the finished product, that is, the long carbon chain nylon material.

[0068] Comparative Example 3

[0069] Weighing materials: first dry the PA1012 high viscosity resin at 80°C for 4 hours for use; then weigh the raw materials: 12 parts of compatibilizer, 0.5 parts of lubricant, 0.3 parts of primary antioxidant, 0.2 parts of auxiliary antioxidant, 0.3 parts of thermal stabilizer, 2 parts of epoxy resin, 5 parts of nylon hot melt adhesive, 1.5 parts of colorant, and 78.2 parts of PA1012 high viscosity resin.

[0070] Mixing: Add weighed PA1012 high-viscosity resin, compatibilizer, epoxy resin, and colorant into a high-speed mixer and mix at high speed for 5 minutes. Then add weighed nylon hot melt adhesive, lubricant, primary antioxidant, auxiliary antioxidant, and thermal stabilizer and continue mixing at high speed for 5 minutes to obtain a mixture.

[0071] Melt extrusion: the mixture is added into a twin-screw extruder, and the temperature of the twin-screw extruder is 210°C, 225°C, 230°C, 235°C, 240°C, 245°C, 245°C, 245°C, 245°C, 245°C, 245°C, 245°C from the first zone to the die head; the screw speed is 400 rpm and the feeding is 35-45 rpm.

[0072] Extrusion pelletizing: The extruded material is cooled, air-dried, pelletized, passed through a vibrating screen, homogenized and packaged in a homogenizing tank to obtain the finished product, that is, the long carbon chain nylon material.

[0073] Comparative Example 4

[0074] First, dry the PA1012 high-viscosity resin at 80°C for 4 hours for use, and then weigh the following raw materials: 0.5 parts of lubricant, 0.3 parts of primary antioxidant, 0.2 parts of secondary antioxidant, 0.3 parts of heat stabilizer, 5 parts of epoxy resin, 5 parts of nylon hot melt adhesive, 1.5 parts of colorant, and 87.2 parts of PA1012 high-viscosity resin.

[0075] Mixing: Add weighed PA1012 high-viscosity resin, compatibilizer, epoxy resin, and colorant into a high-speed mixer and mix at high speed for 5 minutes. Then add weighed nylon hot melt adhesive, lubricant, primary antioxidant, auxiliary antioxidant, and thermal stabilizer and continue mixing at high speed for 5 minutes to obtain a mixture.

[0076] Melt extrusion: the mixture is added into a twin-screw extruder, and the temperature of the twin-screw extruder is 210°C, 225°C, 230°C, 235°C, 240°C, 245°C, 245°C, 245°C, 245°C, 245°C, 245°C, 245°C from the first zone to the die head; the screw speed is 400 rpm and the feeding is 35-45 rpm.

[0077] Extrusion pelletizing: The extruded material is cooled, air-dried, pelletized, passed through a vibrating screen, homogenized and packaged in a homogenizing tank to obtain the finished product, that is, the long carbon chain nylon material.

[0078] Comparative Example 5

[0079] First, the PA1012 high viscosity resin was dried at 80°C for 4 hours for use, and then the raw materials were weighed: 7 parts of compatibilizer, 0.5 parts of lubricant, 0.3 parts of primary antioxidant, 0.2 parts of auxiliary antioxidant, 0.3 parts of thermal stabilizer, 5 parts of nylon hot melt adhesive, 1.5 parts of colorant, and 85.2 parts of PA1012 high viscosity resin.

[0080] Mixing: Add weighed PA1012 high-viscosity resin, compatibilizer, epoxy resin, and colorant into a high-speed mixer and mix at high speed for 5 minutes. Then add weighed nylon hot melt adhesive, lubricant, primary antioxidant, auxiliary antioxidant, and thermal stabilizer and continue mixing at high speed for 5 minutes to obtain a mixture.

[0081] Melt extrusion: the mixture is added into a twin-screw extruder, and the temperature of the twin-screw extruder is 210°C, 225°C, 230°C, 235°C, 240°C, 245°C, 245°C, 245°C, 245°C, 245°C, 245°C, 245°C from the first zone to the die head; the screw speed is 400 rpm and the feeding is 35-45 rpm.

[0082] Extrusion pelletizing: The extruded material is cooled, air-dried, pelletized, passed through a vibrating screen, homogenized and packaged in a homogenizing tank to obtain the finished product, that is, the long carbon chain nylon material.

[0083] The long carbon chain nylon materials prepared in Examples 1-3 and Comparative Examples 1-6 were subjected to performance tests. The test results are shown in Table 1, and the performance test methods and conditions are shown in Table 2.

[0084] Table 1

[0085]

[0086] Table 2

[0087]

[0088]

[0089] Adhesion evaluation: After long-chain nylon and TPE are co-extruded into a double-layer tube (inner layer thickness 1.5mm, outer layer thickness 1mm), thin ring samples are cut at intervals of 300mm. Take 20 samples and observe the interface adhesion of the inner and outer layers under a 200x microscope. If detachment is observed at any point, it is considered unqualified and will not proceed to the next step of testing. The pass rate is required to be 100%.

[0090] The double "85" test means: aging test of samples under specific high temperature and high humidity environment conditions, temperature: 85°C, humidity: 85% RH (relative humidity), test time 1000 hours, and observing the detachment of the inner and outer layers under a microscope. Detachment is considered unqualified.

[0091] Ten samples that have passed the preliminary adhesion test are respectively subjected to a double "85" long cycle test. After the test, the inner and outer layer interface adhesion test is carried out using the same method as above, with a requirement of a 100% pass rate.

[0092] From the results in Table 1, it can be seen that Examples 1-3 used materials consisting of PA1012 high-viscosity resin, epoxy resin, nylon hot melt adhesive and compatibilizer, and the extrusion was smooth. However, since the epoxy resin has a great influence on the fluidity of the material, as the proportion of the epoxy resin increases, the resin fluidity decreases during the extrusion process, and the material strip expands.

[0093] It can be seen from the test results of Examples 1-3 in Table 1 that both the compatibilizer and the epoxy resin are helpful for the interfacial adhesion of the material and have a certain synergistic effect. If the proportion of the compatibilizer is too small, the bonding effect is not good, and if the proportion of the compatibilizer is too large, the material is soft and difficult to shape during the tube extrusion process, and the fusion of the weld line position is not very good.

[0094] From the test results of Examples 1-3 in Table 1, it can be seen that the greater the amount of compatibilizer added, the higher the material impact, the better the low temperature resistance, and the better the flexibility of the pipe, but the tensile strength of the material is reduced, which may affect the bursting pressure of the pipe.

[0095] From the test results of comparative example 1 in Table 1, it can be seen that nylon hot melt adhesive greatly improves the moisture and heat resistance of the material. The qualified rate of the material without nylon hot melt adhesive after double "85" test is reduced from 100% to 35%.

[0096] It can be seen from the test results of comparative example 2 in Table 1 that when the amount of epoxy resin added reaches 13%, the viscosity of the resin increases, the material strips swell after leaving the extruder, the strip breakage phenomenon is serious, and the extrusion fails.

[0097] It can be seen from the results of comparative example 3 in Table 1 that when the amount of epoxy resin added is lower than a certain proportion, the nylon interface activity is insufficient, the adhesion between nylon and TPE is relatively poor, and there are many places on the tube that cannot be adhered.

[0098] According to Example 4 and Comparative Examples 4 and 5, the compatibilizer and epoxy resin have a certain synergistic effect. Using only one of them is not enough for the surface activity and the bonding effect does not meet the requirements. The main reason is that the maleic anhydride group of the compatibilizer has a certain polarity, and the ether bond and hydroxyl group of the epoxy resin are also very strong polar groups. The polar groups of both parties can provide more side chains to improve the wettability and adhesion of the material. At the same time, the epoxy group of the epoxy resin can form a more stable chemical bond with the anhydride group to improve the bonding of the material.

[0099] Although this specification is described according to implementation modes, not every implementation mode includes only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

[0100] Therefore, the above description is only a preferred embodiment of the present application and is not intended to limit the scope of implementation of the present application; that is, all equivalent changes made according to the scope of the claims of the present application are within the protection scope of the claims of the present application.

Claims

1. A long carbon chain nylon material resistant to double 85, characterized in that: It is prepared from the following components in percentage by mass:

2. The double 85 resistant long carbon chain nylon material according to claim 1, characterized in that: The compatibilizer is one or more of grafted POE, grafted EPDM, grafted PP and grafted SEBS.

3. The double 85 resistant long carbon chain nylon material according to claim 1, characterized in that: The lubricant is at least one or more of PETS, OP wax, silicone, silicone oil and silicone amide.

4. The double 85 resistant long carbon chain nylon material according to claim 1, characterized in that: The antioxidant includes a main antioxidant and an auxiliary antioxidant. The main antioxidant is at least one or more of antioxidant 245, antioxidant 1010, antioxidant 1098, and antioxidant 9228. The auxiliary antioxidant is at least one of antioxidant 168 and antioxidant 626.

5. The double 85 resistant long carbon chain nylon material according to claim 1, characterized in that: The heat stabilizer is at least one or more of an inorganic copper salt nylon heat stabilizer, an organic copper salt nylon heat stabilizer, an inorganic phosphate nylon heat stabilizer, an aluminum silicate treated with titanate, and a dipentaerythritol (3-(3.5-tert-butyl-4-hydroxyphenyl) propionate) composite heat stabilizer.

6. The double 85 resistant long carbon chain nylon material according to claim 1, characterized in that: The polyamide resin is PA1012 high-viscosity resin, and its relative viscosity is 4-8.

7. The long carbon chain nylon material resistant to double 85 according to claim 1, characterized in that: The colorant is at least one or more of nylon carrier aniline black masterbatch and PE carrier black masterbatch.

8. The method for preparing the double 85 resistant long carbon chain nylon material according to any one of claims 1 to 7, characterized in that: The following steps are involved: Weigh each component according to mass percentage, mix the polyamide resin, compatibilizer, epoxy resin and colorant evenly, then add lubricant, primary antioxidant, secondary antioxidant, heat stabilizer and nylon hot melt adhesive powder and mix evenly to obtain a mixture; The mixed material is added into the main feeding port of a twin-screw extruder, and after melting, extrusion, cooling, air drying, and pelletizing, an extrusion-grade long carbon chain nylon material resistant to double 85 and capable of adhering to TPE is obtained; Among them, the temperature of the twin-screw extruder from the first zone to the head is 210℃, 225℃, 230℃, 235℃, 240℃, 245℃, 245℃, 245℃, 245℃, 245℃, 245℃, 245℃; the screw speed is 400 rpm and the feeding is 35-45 rpm.

9. An application of a long carbon chain nylon material resistant to double 85 in double-layer co-extrusion materials, characterized in that: The double-layer co-extruded material comprises an inner tube and an outer tube, the inner tube is made of the long carbon chain nylon material as described in any one of claims 1 to 7, and the outer tube is made of TPE resin.

10. The use of the long carbon chain nylon material resistant to double 85 in double-layer co-extrusion materials according to claim 9, characterized in that: The hardness of the TPE resin is 65-70, and its 200H compression rate is less than 2% under the conditions of 110°C and 1.8kN.

Citation Information

Patent Citations

  • Reinforced nylon alloy material capable of being directly bonded with TPE in injection molding way and preparation method thereof

    CN101760009A

  • Graphene-modified nylon special for FDM (fused deposition modeling) and preparation method and application thereof

    CN109438972A

  • High strength wear-resistant nylon composite material for 3D printing and preparation method and application thereof

    CN109777091A

  • Polyamide composite material as well as preparation method and application thereof

    CN116355403A

  • Nylon alloy material with metal adhesion

    CN117757256A

Cited By

  • Adhesive material containing EVOH layer for multilayer nylon tube and preparation method of adhesive material

    CN120424618A

  • Adhesive material for multilayer nylon pipe containing an evo h layer and method for producing the same

    CN120424618B

  • High-epoxy-adhesion long-carbon-chain nylon composition as well as preparation method and application thereof

    CN121249143A